Desenvolvimento de método para determinação da expansão de amido de mandioca - Madeira, Raul Antônio Viana (2017)
The quality of products derived from the cassava starch is impaired by the quality deviations of their raw materials. These failures are associated to lack of control in their processing, in the drying stages over the sun and natural fermentation, in the case of sour cassava starch. When it is desired to improve the production and the qualification of the starch, the main problem is to find indexes that easily describe the quality of the product, being possible to mention, for this, the expansion of the starch. The determination of this expansion in a microwave oven seems to be an interesting alternative to determine this property, and if success is achieved, there will be great savings of time and energy. This experiment had the follows objectives: to collect samples of starch marketed as "cassava starch" and "sour cassava starch" available in the market of Minas Gerais; Analyze them to understand some relations between physical-chemical and technological properties; Establish indicators that can be used in production and marketing; Propose a reliable methodology to determine the property of starch expansion. Seventeen samples of cassava starch marketed in the State of Minas Gerais were collected as cassava starch and sour cassava starch. The centesimal composition, color parameters, expansion, acidity, pH, absolute density, water absorption index and solubility index were determined. The parameters with differences were used in an attempt to propose a classification of commercial starches as cassava starches. The microwave oven expansion methodology was validated through tests of accuracy, precision and robustness. The chemical composition of starch marketed as cassava starch and sour cassava starch is not a usable parameter for determining differences between starches. The specific volume, clarity, titratable acidity, pH, WAI and WSI are important parameters to consider when establishing indicators and differences between marketed starches. It was not possible to classify the samples in cassava starch and sour cassava starch, but it was possible to establish a classification according to the specific volume of the analyzed samples, and to determine the expansion of starches using microwave oven. The methodology proposed was accurate, robust and with close accuracy to other methodologies. It is noteworthy that the method is fast, making it a viable alternative for use in any starchy industries.